Pedology of Mixed Deciduous and Plantation forests in Tarai and Bhawar of Kumaun Himalaya, Uttarakhand - Joshi, Bhasker; Pant, S. C. (Indian Forester, 2014)
The soil samples of two forest types i.e., mixed deciduous type and plantation type were analysed for their physical and chemical properties at Tarai and Bhawar regions of Tarai West Forest Division, Ramnagar, Uttarakhand. Soil colour varied from grayish brown to light brownish gray and soil texture varied from silty clay loam to sandy loam. The result of the present study shows that the higher per cent of water holding capacity, pH, organic carbon, organic matter, total nitrogen, available potassium and available phosphorus was higher in mixed deciduous type forest than in plantation type forest. The pH indicate that the soil of both forest types were acidic in nature.